What Works, What Doesn't? Three Studies Designed to Improve Survey Response. Issue 3 (August 2020) - Sun, Hanyu; Newsome, Jocelyn; McNulty, Jennifer; Levin, Kerry; Langetieg, Pat; Schafer, Brenda; Guyton, John
Over the past few decades, the survey industry has experienced a steady decline in response rates, which has posed numerous challenges for researchers, most notably concerns about nonresponse bias. We present results from three studies conducted in an attempt to increase response rates and reduce nonresponse bias for a U.S. national household survey. We examined design features related to mode (i.e., mail-only vs. web-push), incentive, reminder type, nonresponse follow-up, and messaging. Results showed that a combination of a mail-only approach and the use of US$2 prepaid incentives increased response rates. However, using incentives did not bring into the respondent pool sample members who were less likely to respond. Additionally, we found that the use of a seventh follow-up contact only slightly increased response rates. Finally, we found that the use of a friendly message not only suppressed response rates but also increased potential nonresponse bias for sample members aged 35–48.